Pengaruh Metode Proyek Terhadap Kemampuan Kognitif Anak Di Kelompok B2 Tk Aisyiyah Maccini Tengah - Herman, Herman; Rusmayadi, Rusmayadi; Herman (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2018)
The research problem is 1. How cognitive abilities of children grouped B2 TK Aisyiyah Middle Maccini of Makassar before and after the treatment methods of the project? Cognitive abilities before being given treatment methods of the project can be seen that the children are not able to connect, assess, and expensive. After the child is given treatment methods of the project children are able to connect, assess, and mempertimbangakan something he was doing. 2. Is there any influence tehadap project method cognitive abilities of children grouped B2 TK Aisyiyah Middle Maccini Makassar City? the purpose of this study was to determine the effect of the methods of the project on children's cognitive abilities grouped B2 TK Aisyiyah Middle Maccini Makassar. Activity methods of the projects is Grouping geometric shapes, sorting numbers 1-20, construct beam patterns. The approach used in this study is the quantitative approach. This type of research is a simple experiment. There are two variables that will be examined in this study is the independent variable and the dependent variable. One study design with GroupPretest-posttest design. Operational definitions of variables. Population and sample in this study amounted to 16 children. The technique of collecting data through observation and documentation. Data collection procedures done through the planning, provision of pretest, giving treatment, posttest administration and analysis of results. Data analysis technique used is different Wilcoxon test. The results showed that the cognitive abilities of children increased acquisition value than before the treatment. From the research carried out showed that the cognitive abilities of children increased acquisition value than before given treatment to the value T count (136)> T table (30) and Z count (3:51)> Z table (1.645), so that the hypothesis is accepted , It can be concluded that there is influence of the methods of the project on children's cognitive abilities grouped B2 TK Aisyiyah Middle Maccini Makassar